Disparate data integration case for connected factories using timestamps - Risch, Quinn D; Milner, Lance E; Maksi, Larissa C; Lynch, Kevin J (Open Science Journal, 2023)
Manufacturing data integration of machine, process, and sensor data from the shop floor remains an important issue to achieve the anticipated business value of fully connected factories. Integrated manufacturing data has been a hallmark of Industry 4.0 initiatives, because integrated data precipitates better decision-making for cost, schedule, and system optimizations. In this paper, we extend work on optimizing manufacturing costs, describing an algorithm using timestamps to integrate previously unassociated quality and test information, enabling us to better identify and eliminate redundant tests. Results are provided and discussed, and we suggest the approach described may be valuable for some types of heterogeneous manufacturing data integration where timestamps and event chronologies are available.